ANALYSIS OF TECHNOLOGICAL EFFICIENCY OF REPAIR WORKS AND METHODS OF INCREASE OF OIL AND GAS EXPLORATION - Татарин, Галина Василівна; Акульшин, Олексій Олександрович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In an environment where the majority of the deposits are in the final stages of development and basic supplies is difficult to extract, the possibility of extracting more oil is in the main for oil and gas industry. Methods to increase oil recovery are expensive and require a justification for each of the fields. Selected methods that have been used for 50 years in the fields of Ukraine. There have been given the analysis of repair works on two deposits of different OGEM. The most effective methods of act on under bottom area of layer are chosen and works after renewal of the mode of operations of mining hole and appraised their efficiency by a technological formula. In- formation is confirmed evidently and tabular. Recommendations are indi- cated in relation to perspective methods which it is possible to apply for the row of similar deposits.